PENGARUH PENDEKATAN METAPHORICAL THINKING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK - Abdillah, Vitta Oktavina; Supratman, Supratman; Dewi, Sinta Verawati; Mansyur, Muhamad Zulfikar (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2023)
This research aims to determine the effect of the metaphorical thinking approach on students' mathematical critical thinking abilities and determine the percentage of students' mathematical critical thinking abilities who use the metaphorical thinking approach. The method used is the experimental method, namely Pretest-Posttest Control Group Design. The population in the study was all students in class VIII of SMP Negeri 1 Tasikmalaya. The samples in the research were students in class VIII G as the experimental class and class VIII A as the control class. The sample technique uses random assignment. The instrument used is a description test of mathematical critical thinking abilities. Data analysis techniques include descriptive statistics and inferential statistics by analyzing and measuring students' mathematical critical thinking skills using IBM SPSS Statistics 24. Normality test using Shapiro Wilk, homogeneity test using Levene's, mean difference test (right side) using Independent Sample T- Test, and the Mann Whitney test. Based on the results of data analysis, it can be concluded that there is an influence of the metaphorical thinking approach on students' mathematical critical thinking abilities. The mathematical critical thinking ability of students with a metaphorical thinking approach is in the high category 40.625%, medium 40.625%, low 18.75%, and the overall average score is 58% in the medium category.